UNIT 15E.2 Growth and Quantification of MERS‐CoV Infection. Issue 1 (1st May 2015) - Coleman, Christopher M.; Frieman, Matthew B.
Abstract : Middle East respiratory syndrome coronavirus (MERS‐CoV) is an emerging highly pathogenic respiratory virus. Although MERS‐CoV only emerged in 2012, we and others have developed assays to grow and quantify infectious MERS‐CoV and RNA products of replication in vitro. MERS‐CoV is able to infect a range of cell types, but replicates to high titers in Vero E6 cells. Protocols for the propagation and quantification of MERS‐CoV are presented. © 2015 by John Wiley & Sons, Inc.